One‐Pot Synthesis of Multifunctional Polymers by Light‐Controlled Radical Polymerization and Enzymatic Catalysis with Candida antarctica Lipase B. Issue 23 (9th September 2013) - Hrsic, Emin; Keul, Helmut; Möller, Martin
Abstract : The preparation of multifunctional polymers and block copolymers by a straightforward one‐pot reaction process that combines enzymatic transacylation with light‐controlled polymerization is described. Functional methacrylate monomers are synthesized by enzymatic transacylation and used in situ for light‐controlled polymerization, leading to multifunctional methacrylate‐based polymers with well‐defined microstructure. Abstract : Multifunctional methacrylate‐based polymers with well‐defined microstructure and block copolymers are prepared with a straightforward one‐pot reaction process that combines enzymatic transacylation, which catalyzes the synthesis of functional monomers, with lightcontrolled polymerization (which is used for in situ polymerization of functional monomers).